Household Behaviour Towards Waste Recycling in Ampang Jaya and Subang Jaya, Selangor - Richardson, Octania P. (2005)
In order to achieve the statutory target for recycling, one of the waste management strategies is to take into account household recycling effort, perceptions and their attitudes towards the recycling scheme. However, there are not many published reports on the perceived effectiveness and public attitudes towards such schemes. Thus, it is important to consider these factors given that recycling schemes are dependent upon the voluntary behaviour of the public. This research was carried out to evaluate the public's perception towards the recycling scheme. Two areas have been chosen for the study and face-to-face interviews were carried out to compare households recycling participants' behaviours towards recycling scheme. In addition the study was also carried out to identify the barriers, level of incentives and traits of recycling participants and nonrecycling participants. Result from this study would help the local authorities in implementing suitable waste management systems. In this study and based on the survey of 250 households in Subang Jaya and 250 households in Ampang Jaya, the results demonstrated that there was a significant relationship between the number of recycling participants and the number of recycling centres in their area. The results also showed that 68% of the households resided in Subang Jaya took part in recycling. Subang Jaya is known as a better-stmctured housing neighbourhood with more recycling facilities. Ampang Jaya however, had fewer recycling centres than Subang Jaya. The study discovered only 43% of households participated in recycling activities. A statistical test showed a significant difference in the number of recycling participants between the two study areas. There were very few respondents who described rubbish with recycling or positive reference to recycling. On the other hand, 55.2% respondents of Ampang Jaya and 50% from Subang Jaya had propensity to relate rubbish as something negative such as; nuisance, useless, unwanted and something they urgently want to dispose of, rather than what they could do to reduce or manage them. The result of this study found that most households understood the definition, benefit of recycling and the duties they were required to perform as consumers to help managing their waste. Thus, education in recycling was not the main factor prevented them in taking part in recycling. The main factor for not recycling stated by non-recycling participants of Ampang Jaya was the location of the recycling centres. As mentioned by non-recycling participants in Ampang Jaya, the longer the distance between the recycling centre and the area they live, the harder it was for them to be able to take part in the recycling programme. The main factor for indolence towards recycling mentioned by nonrecycling participants in Subang Jaya was that there were no door-to-door recycling pick-up services available. Non-recycling participants from both areas also agreed that door-to-door pick up service with regular time schedule would be very helpful for those with inconvenient time and for those with no transportation. Further research is required to identify more clearly the reasons for non-participation in local authority recycling schemes and to identify mechanisms for the improvement of participation rates.